EFL Learners’ Interests and Attitudes toward Flipped Classroom Method in Speaking Classes - Abd. Rahman; Sahril Nur; Muhaiminah Akib (IAIN Syekh Nurjati Cirebon, 2023)
EFL learners’ interests and attitudes now are the primary concern of the flipped-classroom method in English language teaching in tertiary education. This research aims to identify the students' level of interest and attitudes toward flipped classrooms in speaking. The mix-method called QUAN-Qual explanatory sequential design used to understand and answer research questions simultaneously. The participants took from all third-semester students who have experienced the flipped-classroom method during six months of study to improve their speaking skills. The interests and attitudes questionnaires were used and scoring based on the Likert Scale. The quantitative data analyzed through descriptive statistics to determine the frequency, percentage, means, and standard deviation using the SPSS version 26, and the qualitative data transcribed and categorized based on the students' interests and attitudes towards the flipped-classroom method. Both quantitative and qualitative analysis strongly demonstrated that most participants have a high interest and positive attitude. Furthermore, self-confidence, a challenging learning atmosphere, and an efficient learning method were three main factors that triggered EFL learners' interest and attitude.